A systematic review of the communication of dangers associated with climate change - Adanlawo, Eyitayo Francis; Chaka, Mpho (International Journal of Innovative Research and Scientific Studies, 2025)
The idea of disaster communication is frequent in conversations about climate change. For this reason, it is crucial to communicate the dangers of climate change to communities. This study is necessary to increase human capability, mainly through effective disaster communication, in order to assist society in developing the most effective long-term defense against the threats of climate change. The goal is to assist in creating strategies that will help society better deal with the effects of climate change. This study systematically reviewed past studies on climate change. The review revealed that climate change can enhance the prevalence of diseases, dwindling water resources, and loss of biodiversity. The study recommends that prior to a disaster event, mitigation activities could assist in lessening vulnerability to disaster impacts like property loss and fatalities. Minimizing losses during a disaster occurrence depends on comprehending and responding appropriately to warning messages. This study came to the conclusion that while sharing responsibility with citizens is the most effective strategy, disaster communication is crucial in efforts to reduce and manage the effects of climate change. As a result, addressing the changes and disseminating information about climate change requires an integrated approach. Communication then has to be a two-way process where society contributes to the formulation of strategies that affect their daily lives.